Masā’il al-Muhtadī li Ikhwān al-Mubtadī: Implikasi Pedagogis Model Pembelajaran Tarekat dalam Praktik Pendidikan - Maesaroh Lubis (Masyarakat Pernaskahan Nusantara, 2015)
Masā’il al-Muhtadī li Ikhwān al-Mubtadī is a monumental work of the 16th century by Shaikh Daud bin Ismail bin Mustafa Rumî knownas Baba Dawud. This article discusses various important thoughts of Baba Dawud about neosufisme that obtained from his teacher, Abd. Rauf As-Sinkili. Baba Dawud want to introduce the image of tarekat can be justified because it is built on a solid foundation of sharī‘ah. When the controversial wujūdīyah is present, Masā’il al-Muhtadī has offered tarekat as a learning media to understanding Islam. Baba Dawud assumes that the perfection of life will be obtained after the mubtadī understand Islam through sharī‘ahand refine it through tarekat. This thought makes Masā’il al-Muhtadī has an important position in the context of Islamic education in the Malay world. Masā’il al-Muhtadī is a living manuscript that much copied and studied in Islamic educational institutions in Indonesia and Southeast Asia. === Masā’il al-Muhtadī li Ikhwān al-Mubtadī adalah teks monumental abad ke-16 karya Shaikh Daud bin Ismail bin Mustafa Rumî, dikenal dengan Baba Dawud. Artikel ini menguraikan pemikiran-pemikiran penting Baba Dawud tentang neosuësme yang didapatkan dari gurunya, Abd. Rauf As-Sinkili. Baba Dawud ingin memperkenalkan citra ajaran tarekat yang dapat dipertanggungjawabkan karena dibangun di atas pondasi kokoh syariat. Ditengah kehadiran paham wujūdīyah yang dianggap kontroversial, Masā’il al-Muhtadī menawarkan tarekat sebagai media pembelajaran alternatif dalam memahami Islam. Baba Dawud menganggap bahwa kesempurnaan hidup akan didapatkan setelah seorang mubtadī mengawali pemahaman keislamannya melalui tahap syariat dan memantapkannya dalam kegiatan tarekat. Pemahaman ini membuat Masā’il al-Muhtadī memiliki kedudukan penting dalam konteks pendidikan Islam di dunia Melayu. Masā’il al-Muhtadī merupakan living manuscript yang banyak disalin dan dikaji di lembaga-lembaga pendidikan Islam di Indonesia dan Asia Tenggara.